2018
DOI: 10.3389/fphar.2018.00696
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific iPSC-Based Models of Huntington’s Disease as a Tool to Study Store-Operated Calcium Entry Drug Targeting

Abstract: Neurodegenerative pathologies are among the most serious and socially significant problems of modern medicine, along with cardiovascular and oncological diseases. Several attempts have been made to prevent neuronal death using novel drugs targeted to the cell calcium signaling machinery, but the lack of adequate models for screening markedly impairs the development of relevant drugs. A potential breakthrough in this field is offered by the models of hereditary neurodegenerative pathologies based on endogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…It is defined by deep gray matter volume loss caused by the destruction of neurons in the substantia nigra, leading to dopamine deficiency in the basal ganglia. PD affects 1-2% Lotharius et al, 2005;Van Vliet et al, 2008;Zhang et al, 2014;Smirnova et al, 2016;Harischandra et al, 2019;Taylor-Whiteley et al, 2019Tan et al, 2018 Amyotrophic lateral sclerosis Pansarasa et al, 2018Chen et al, 2014Fujimori et al, 2018Dimos et al, 2008Burkhardt et al, 2013;Sareen et al, 2013Smith et al, 2015Krencik et al, 2017;Osaki et al, 2018. Huntington's disease Bidollari et al, 2018Szlachcic et al, 2017An et al, 2012Camnasio et al, 2012;Juopperi et al, 2012;Nekrasov et al, 2016;Vigont et al, 2018;Mehta et al, 2018Virlogeux et al, 2018 Spinal muscular atrophy Not available Not available Ebert et al, 2009;Fuller et al, 2015;Zhang et al, 2017a;Valetdinova et al, 2019. Hor et al, 2018 Spinocerebellar ataxia Kumar D. et al, 2018;Maguire et al, 2019Wang et al, 2015Xia et al, 2013Marthaler et al, 2016;Nayler et al, 2017;Sun et al, 2018;Chuang et al, 2019;…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…It is defined by deep gray matter volume loss caused by the destruction of neurons in the substantia nigra, leading to dopamine deficiency in the basal ganglia. PD affects 1-2% Lotharius et al, 2005;Van Vliet et al, 2008;Zhang et al, 2014;Smirnova et al, 2016;Harischandra et al, 2019;Taylor-Whiteley et al, 2019Tan et al, 2018 Amyotrophic lateral sclerosis Pansarasa et al, 2018Chen et al, 2014Fujimori et al, 2018Dimos et al, 2008Burkhardt et al, 2013;Sareen et al, 2013Smith et al, 2015Krencik et al, 2017;Osaki et al, 2018. Huntington's disease Bidollari et al, 2018Szlachcic et al, 2017An et al, 2012Camnasio et al, 2012;Juopperi et al, 2012;Nekrasov et al, 2016;Vigont et al, 2018;Mehta et al, 2018Virlogeux et al, 2018 Spinal muscular atrophy Not available Not available Ebert et al, 2009;Fuller et al, 2015;Zhang et al, 2017a;Valetdinova et al, 2019. Hor et al, 2018 Spinocerebellar ataxia Kumar D. et al, 2018;Maguire et al, 2019Wang et al, 2015Xia et al, 2013Marthaler et al, 2016;Nayler et al, 2017;Sun et al, 2018;Chuang et al, 2019;…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…These currents were upregulated compared with wildtype iPSC-based GABAergic MSNs. Thapsigargin-induced intracellular Ca 2+ store depletion in iPSC-based GABAergic MSNs resulted in the simultaneous activation of both I CRAC and I SOC (Vigont et al, 2018 ).…”
Section: Dysregulation Of Soce Causes Synaptic Loss In Hd Modelsmentioning
confidence: 99%
“…This compound also potently stabilized SOC entry in HD iPSC-based GABAergic MSNs (Nekrasov et al, 2016 ), thus confirming its specificity in neurons that were reprogrammed from fibroblasts from HD patients. The molecular target of EVP4593 is still unknown, but recent data showed that EVP4593 equally affected different SOC channels in HD iPSC-based GABAergic MSNs, suggesting that this compound could target SOCE regulatory proteins that are involved in both I CRAC and I SOC (e.g., STIM proteins) (Vigont et al, 2018 ). Huntington's disease iPSC-based GABAergic MSNs that were characterized by both excessive SOCE and progressive HD pathology (Nekrasov et al, 2016 ) were recently proposed to serve as a platform for personal drug screening in HD (Bezprozvanny and Kiselev, 2017 ; Vigont et al, 2018 ).…”
Section: Potential Therapeutic Strategies To Stabilize Soce In Hdmentioning
confidence: 99%
“…Additionally, knockdown of TRPC1, TRPC6, Orai1, or Orai2 also shows protective effects on medium spiny neuron spines in HD model mice (Wu J. et al, 2018). As such, SOCs have been studied as a potential therapeutic target for HD, with the effect of the potential anti-HD drug EVP4593 on calcium regulation via these channels being investigated in recent years (Wu et al, 2016;Vigont et al, 2018).…”
Section: Socs In Huntington's Disease (Hd)mentioning
confidence: 99%